2009
DOI: 10.1177/0743558409350501
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Hopefulness in Tanzania

Abstract: This study compares hope in street youth, former street youth, and school youth (aged 12-18) in Tanzania. Responding to Snyder’s hope theory, the author argues that not only personal agency but also the stability of living context (street, shelter, home) shapes hopefulness. Employing qualitative and quantitative analyses, the author presents a framework that shows considerable differences by youth group in hope conceptualizations. Youth in unstable environments avoid hope to circumvent failure and instead attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This observation has been noted also by a recent study, also using the Snyder scale among youth in Tanzania (Nalkur, 2009). …”
Section: Ethnographic Datasupporting
confidence: 52%
“…This observation has been noted also by a recent study, also using the Snyder scale among youth in Tanzania (Nalkur, 2009). …”
Section: Ethnographic Datasupporting
confidence: 52%
“…The keywords (terms) used were adolescents, middle school students, high school students, college students, hope, and hopefulness. Both hope and hopefulness are used interchangeably in the literature (Nalkur, 2009), and in concept analyses (Benzein & Saveman, 1998; Sachse, 2007; Stephenson, 1991); studies of both were included in these meta-analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Recent theoretical views have suggested that adolescent hope focuses on a possibility, a reflection of life’s opportunities, and a future orientation, all of which are embedded in a community where hope can thrive and operate (Nalkur, 2009; te Riele, 2010). According to Nalkur, descriptions of adolescent hope, also referred to as hopefulness, may exist across all cultural contexts.…”
mentioning
confidence: 99%
“…In contrast, some literature casts a derogatory tone over passive hope that suggests it is equivalent to a "false" hope (Jacoby 2003, Osika 2019). Passive hope is often associated with periods of inactivity (Bright 2011, Govier 2011, Musschenga 2019, a lack of agency (Andersson 2016, Lybbert and Wydick 2018, https://www.ecologyandsociety.org/vol28/iss2/art14/ Musschenga 2019) or motivation (Miceli and Castelfranchi 2010), fantasizing without a plan to realize the imagined outcome (Miceli and Castelfranchi 2010), "a temporal structure of unreflective being-in-the-world" (de Graaf 2016:604), and a reliance on others, whether individuals (Nalkur 2009), groups (Macy andJohnstone 2012, Yunkaporta 2019), or some form of spiritual intervention (Jacoby 2003). Passive hope is also described as patiently waiting for things to become better (Lybbert and Wydick 2018) or harm-avoidance (Fu et al 2018).…”
Section: Introductionmentioning
confidence: 99%